Soluble fms-like tyrosine kinase-1 detection kit as well as preparation method and application thereof - WU HANQI; QIN JING; ZHAN WENWEN; WANG BAOSHENG (2022)
The invention relates to a soluble fms-like tyrosine kinase-1 detection kit as well as a preparation method and application thereof, the inventor detects soluble fms-like tyrosine kinase-1 by adopting a double-antibody sandwich method combined with a magnetic particle chemiluminescence technology, and finds that an immune micro-magnetic particle preparation method optimized by the inventor is adopted. A soluble fms-like tyrosine kinase-1 chemiluminescence immunoassay kit is formed by the prepared placenta growth factor capture antibody magnetic particles and an alkaline phosphatase labeled placenta growth factor detection antibody which is further prepared by the inventor through cross-linking agents DTBP and DTT and a sealing agent MMTS in a specific proportion. According to the present invention, the detection can be automatically completed by using the full-automatic chemiluminescence immunoassay analyzer as the detection tool, the detection performance is significantly improved, the detection sensitivity